Lessons in chemistry [large type] - Garmus, Bonnie (Random House Large Print, in association with Doubleday, a division of Penguin Random House LLC, 2022)
"Chemist Elizabeth Zott is not your average woman. In fact, Elizabeth Zott would be the first to point out that there is no such thing as an average woman. But it's the early 1960s and her all-male team at Hastings Research Institute takes a very unscientific view of equality. Except for one: Calvin Evans; the lonely, brilliant, Nobel-prize nominated grudge-holder who falls in love with--of all things--her mind. True chemistry results. Like science, though, life is unpredictable. Which is why a few years later Elizabeth Zott finds herself not only a single mother but also the reluctant star of America's most beloved cooking show, Supper at Six. Elizabeth's unusual approach to cooking ("combine one tablespoon acetic acid with a pinch of sodium chloride") proves revolutionary. But as her following grows, not everyone is happy. Because as it turns out, Elizabeth Zott isn't just teaching women to cook. She's daring them to change the status quo"--Page 4 of cover.